PARTISIPASI PEREMPUAN DALAM IMPLEMENTASI PROGRAM DANA DESA DI KAMPUNG ARMO PESISIR DISTRIK SARMI KABUPATEN SARMI - Sarce S. Kreeuw; Yosephina Ohoiwutun (Universitas Cenderawasih, 2021)
This study aims to describe and analyze women's participation in the Implementation of the Village Fund Program in Armo Pesisir Village, Sarmi District, Sarmi Regency and describe the factors that influence it. The research method used is qualitative descriptive. Data collection techniques in the form of interviews and observations. Data analysis includes data reduction, data exposure, and drawing conclusions. The results showed that the form of women's participation in the Implementation of the Village Fund Program in Armo Pesisir Village, Sarmi District, Sarmi Regency. Women's participation contributes to every stage of the management of the Village Fund Allocation, starting from planning, implementation, administration, reporting and accountability. It's just that at the stage of administration and accountability women are not directly involved, because it is the authority and responsibility of the BPK, but in the planning, implementation and reporting stages, women participate. Then it is related to the form of women's participation in the form of giving voice to fight for their rights and the open access provided. And the level of participation starts from delegation, partnership, consultation and information. Then, the supporting factors are the level of education, social solidarity, responsibility and intense information dissemination. Then the inhibiting factors are cultural factors, misunderstandings, and mutual suspicion from the community.